Impact of labor and input costs on the competitiveness of apple farms: A case study from Korça region, Albania - Sosoli, Ilir; Keco, Remzi; Tomorri, Ilir (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of labor and input costs on the profitability and competitiveness of apple farms in the Korça region of Albania. Drawing on primary data collected from 125 apple farms during the 2024 growing season and secondary data from national and regional sources, the study evaluates how cost variations impact farm-level economic outcomes. Findings reveal that labor and input costs jointly constitute over 90% of total production expenses, with labor averaging 40–45% and inputs 50–55% of total costs. Cost fluctuations, particularly during harvest and fertilizer procurement periods, have a substantial effect on unit production costs and market competitiveness, as measured by the cost-competitiveness ratio. This study highlights the crucial role of labor and input costs in determining the competitiveness of apple farms. Input costs represent a continuous and significant challenge for farmers in their activities. The study concludes that to sustain competitiveness, apple farmers in Korça must adopt cost-reduction strategies and benefit from targeted policy support such as labor subsidies and cooperative input purchasing.